Whence they came : deportation from Canada 1900-1935 - Roberts, Barbara Ann, 1941-1998 (CEL - Canadian Publishers Collection., 1988)
Until recently, immigration policy was largely in the hands of a small group of bureaucrats, who strove desperately to fend off "offensive" peoples. Barbara Roberts explores these government officials, showing how they not only kept the doors closed but also managed to find a way to get rid of some of those who managed to break through their carefully guarded barriers. Robert's important book explores a dark history with an honest and objective style.